(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The purpose of this study is to investigate the differences in perceptions, i) on the usefulness of costing information produced by ABC and the traditional costing system, and ii) between users and preparers. The respondents were selected using disproportionate stratified random sampling method among staff in the biggest public university in Malaysia with a multi-campus university system. Twelve branch campuses across the country. The data was collected using structure postal questionnaires that were distributed to 153 respondents across all of their campuses. The results indicated that respondent perceived the information produced by ABC system as of higher functionality as compared to the traditional costing system information. The finding also showed that there was no significance difference between users and prepares with regards to the quality of ABC system, but users perceived the ABC information is of higher functionality than do the preparers.